Effect of saline and water stress and of early aging on the "algaroba" seed germination - Perez, Sônia Cristina Juliano Gualtieri de Andrade; Tambelini, Mariângela (Pesquisa Agropecuaria Brasileira, 1995)
Mesquite (Prosopis juliflora (Sw.) D.C.) seedlings stored for five years in a refrigerator, submitted to a viability test, presented 99% of germination. Later, the effects of water and salt stress were observed using NaCl, CaCl2, Na2S04 and manitol solutiol in several osmotic potentials: 0.0; -0.3; -0.6; -0.9; -1.2 and -1.5 MPa. The seedlings' vigor was observed using the length of the hypocotyl and radicle. A significant decrease in germination was verified beginning with -0.3 MPa for NaCl and -0.6 MPa for the other salts. Na2S04 solutions resulted in a significant reduction in the seedlings' length. Mesquite seeds presented resistance to an accelerated aging.